Rancang Bangun dan Pelatihan Penggunaan Sistem Administrasi Taman Pendidikan Al-Quran Al Mursyidien Surabaya - Rani Rotul Muhima; Andy Rachman; Rahmi Rizkiana Putri; Farida Farida; Danang Haryo Sulaksono (JPP IPTEK (Jurnal Pengabdian dan Penerapan IPTEK), 2019)
The administration of TPA Al-Mursyidien was still manual. TPA, which is located on Jalan Semolowaru No. 114-118, Semolowaru Surabaya, has had a number of students to hundreds of santri. This is troublesome for the teacher who is also the TPA administration. TPA already has information and communication technology infrastructure facilities but is still not optimally utilized. In fact, ICT can be used to assist TPA’s administration management. Based on these problems, at the ITATS Informatics Engineering Program (PPM) was made application called the "Al-Mursyidien APP". This application is used as a database of santri, instructors, management of data in and out of students, in and out of lecturers, management of student tuition fees and management of teacher payroll at TPA Al-Mursyidien In addition to making these applications, training on the application is used as well as making modules for application usage "APP's Al-Mursyidien".